2015
DOI: 10.14720/aas.2015.105.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil and foliar applications of iron and zinc on flowering and essential oil of chamomile at greenhouse conditions

Abstract: In order to study the effects of soil and foliar applications of iron (Fe) and zinc (Zn) on flowering, flower yield and essential oil production of German chamomile a pot experiment was conducted under greenhouse conditions at the Faculty of Agriculture, University of Tabriz, Iran in 2012. The experiment was arranged as completely randomized design with 12 treatments and three replications. ), T 9 : T 5 +T 7 , T 10 : T 5 +T 8 , T 11 : T 6 +T 7 , T 12 : T 6 +T 8 . The foliar spraying was done two times during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Researchers have noted that Zn is an important element in plant development and can affect flowering (Butnariu et al, 2008;Srivastava and Singh, 2009;Hada et al 2014;Nasiri and Najafi, 2015), which was confirmed by the current results. Srivastava and Singh (2009) indicated that a foliar application of Zn at various levels (100 g, 200 g, 300 g) significantly induced flowering intensity.…”
Section: Discussionsupporting
confidence: 85%
“…Researchers have noted that Zn is an important element in plant development and can affect flowering (Butnariu et al, 2008;Srivastava and Singh, 2009;Hada et al 2014;Nasiri and Najafi, 2015), which was confirmed by the current results. Srivastava and Singh (2009) indicated that a foliar application of Zn at various levels (100 g, 200 g, 300 g) significantly induced flowering intensity.…”
Section: Discussionsupporting
confidence: 85%
“…The favourable ef-fect of P fertilization was investigated by numerous researchers on flowering of some ornamentals such as chrysanthemum (Kato and Takel, 1989), gerbera (Mohamed, 1992) and violet (El-Sallami, 1996). Other scientists reported the promotive effect of Zn on flowering of marigold (Omer, 1992), narcissus (El-Sallami, 1997) and chamomile (Nasiri et al, 2010).…”
Section: Earliness and Flowering Periodmentioning
confidence: 98%
“…The favorable effects of P fertilization on growth and flowering were investigated by numerous researchers on many plants such as chrysanthemum (Kato and Takel, 1989), gerbera (Mohamed, 1992), violet and florists cineraria (El-Sallami, 1996& 2001, prunus (Balal et al, 2011) and strawberry (Mo-hamed et al, 2011). Other works concluded that adequate Zn nutrition is essential for more vigorous plants and had better growth and quality than other plants severely Zndeficient (Moraghan and Grafton, 2003;Mirvat et al, 2006;Nasiri et al, 2010;Carolina et al, 2011 andObaid andAl-Hadethi, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mean table (9) shows that the dry weight of flower was significantly affected by the foliar application of zinc, iron and their interaction. The maximum dry weight of flowers (3.06 g) of marigold was noted in those plots which were treated with 0.…”
Section: Dry Weight Of Flower (G)mentioning
confidence: 99%
“…Zinc is also known as an important constituent for many growth promoting substances such as for the synthesis of tryptophan and a precursor of indole acetic acid. It has been reported that the essential oil percentage, oil yield and flowers yield of chamomile was increased with the application of zinc [9]. Iron is also important micro nutrients which plays an important role in the respiration and photosynthesis and also affects its properties.…”
Section: Introductionmentioning
confidence: 99%